Simulation and experimental validation of gain-control parallel hybrid fiber amplifier - Ali M.H.; Abdullah F.; Jamaludin M.Z.; Al-Mansoori M.H.; Al-Mashhadani T.F.; Abass A.K. (Optical Society of Korea, 2023)
We demonstrate a simulation of a parallel hybrid fiber amplifier in the C+L-band with a gain controlling technique. A variable optical coupler is used to control the input signal power for both EDFA and RFA branches. The gain spectra of the C+L-band are flattened by optimizing the coupling ratio of the input signal power. In order to enhance the pump conversion efficiency, the EDFA branch was pumped by the residual Raman pump power. A gain bandwidth of 60 nm from 1530 nm to 1590 nm is obtained with large input signal power less than -5 dBm. The gain variation is about 1.06 dB at a small input signal power of -30 dBm, and it is reduced to 0.77 dB at the large input signal power of -5 dBm. The experimental results show close agreement with the simulation results. © 2014, Optical Society of Korea. All rights reserved.